2007
DOI: 10.1029/2006jd007494
|View full text |Cite
|
Sign up to set email alerts
|

Regional transport and dilution during high‐pollution episodes in southern France: Summary of findings from the Field Experiment to Constraint Models of Atmospheric Pollution and Emissions Transport (ESCOMPTE)

Abstract: In the French Mediterranean basin the large city of Marseille and its industrialized suburbs (oil plants in the Fos-Berre area) are major pollutant sources that cause frequent and hazardous pollution episodes, especially in summer when intense solar heating enhances the photochemical activity and when the sea breeze circulation redistributes pollutants farther north in the countryside. This paper summarizes the findings of 5 years of research on the sea breeze in southern France and related mesoscale transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 85 publications
7
43
0
Order By: Relevance
“…They also allowed the analysis of the contribution of the sea-breeze to the regional transport of humidity (Bastin et al 2005a and pollutants Menut et al 2005) and the evaluation of existing sea-breeze scaling laws with the large body of observations collected during the campaign . A review of the main results from this campaign can be found in Drobinski et al (2007). Such literature enables a critical evaluation of the HyMeX/MED-CORDEX simulations described hereafter.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also allowed the analysis of the contribution of the sea-breeze to the regional transport of humidity (Bastin et al 2005a and pollutants Menut et al 2005) and the evaluation of existing sea-breeze scaling laws with the large body of observations collected during the campaign . A review of the main results from this campaign can be found in Drobinski et al (2007). Such literature enables a critical evaluation of the HyMeX/MED-CORDEX simulations described hereafter.…”
Section: Measurementsmentioning
confidence: 99%
“…Two major flow regimes alternate during summertime in this region, the Mistral and Tramontane northerly-northwesterly winds and the sea breeze induced by the sea land temperature contrast which advects moisture and pollutants as far as 100 km inland thus affecting the inhabitants leaving in the countryside (e.g. Bastin et al 2007;Drobinski et al 2007). A large number of data were collected (meteorological data from surface weather stations, radiosondes and constant volume balloons, wind profiles from lidar, radar and sodar profilers, … ; see Cros et al 2004 for more details) and meso-scale numerical simulations performed.…”
Section: Measurementsmentioning
confidence: 99%
“…The surface temperature during the passage of Marseille's sea-breeze front has been found to be oscillatory Drobinski et al, 2007). Cold air transported inland due to the sea breeze results in temporarily increased stability over the land (isentrope inclination allows the seabreeze flow to run along the slope, and adiabatic cooling associated with rising air retards the flow).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution modelling studies have suggested that sea and lake breezes interact with Marseille's VOC emissions to create high ozone episodes (Lasry et al, 2005). Sophisticated urban heat island modelling for the same region suggests that Marseille's urban heat island circulation is affected by the sea breeze: the urban circulation when the city was affected by sea breezes was suppressed relative to instances of synoptic flows originating over the land (Lemonsu et al, 2006a;Drobinski et al, 2007). Work by the same group (Lemonsu et al, 2006b) also suggested the presence of "deep" and "shallow" sea-breeze circulations, the former inhibited by topography, the latter enhanced by topography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation